Higher Education in the Middle East and North Africa: Exploring Regional and Country Specific Potentials - Lai, Yew Meng; Abdul Razak Ahmad; Chang, Da Wan; Bait al Amanah (Springer Science , Business Media Singapore Pte Ltd., 2016)
This book explores the prospects for higher education development in the Middle East and North African (MENA) region. Adopting a South-South perspective (from the viewpoint of a developing country), it seeks to promote a deeper understanding of this colourful and highly diverse, yet volatile region. As such, it examines six selected MENA countries that serve as case studies for identifying the gaps and challenges as well as their potentials in terms of higher education development. Based on expert interviews and focus-group discussions with more than 85 individuals across the six countries and complemented by related facts and figures from both international and national documents, it presents an in-depth discussion and analysis of the countries’ respective political, security, and economic situations. These serve as preconditions for the cultivation of an environment conducive to facilitating the advancement of higher education. It also provides a critical overview of higher education in these countries, notably in terms of the current national system, legislative framework, accreditation, quality assurance, recognition concerns, and other critical issues that enable and/or constrain the development of their respective higher education sectors, and that of the region, as a whole.